Implementasi Model PBL Berbantuan Media PAPIPA Pada Pembelajaran Pendidikan Pancasila Guna Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas IV-B SDN Junrejo 01 Kota Batu - Cherry Rinaldi; Subianto Karoso (Journal of Practice Learning and Educational Development, 2025)
Sekolah Indonesia Riyadh (SIR) plays a pivotal role in supporting the Indonesia Emas 2045 vision through the provision of high-quality global education. This institution integrates national and international curricula to prepare young generations for global challenges while preserving their national identity. This study explores key elements supporting education at SIR, including global education, curriculum integration, multicultural environments, character education, and technology utilization. The findings reveal that SIR's holistic approach enhances tolerance, cross-cultural understanding, and students' academic and non-academic skills. The multicultural environment at SIR enriches students' learning experiences, while character education instills values of integrity, responsibility, and respect for diversity. Additionally, technology utilization improves learning effectiveness and information access. The study concludes that SIR not only supports Indonesia's overseas education goals but also shapes innovative, competent, and globally competitive young generations.